HOUSE PRICING DETERMINANTS FROM BUYERS PERSPECTIVE IN JEDDAH, SAUDI ARABIA - Razan Jambi; Karima Saci (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This paper aimed to investigate the price/rent determinants in Jeddah, Saudi Arabia to better understand the buyer’s preferences, attitude and mentality toward housing appraisal and valuation. In doing so an online survey was conducted through simple random sampling, the survey was taken by 277 people. The research aimed to conduct a regression analysis as a methodology for analyzing collected data. Major findings of this study are considering the price of property, location of property, safety standards implemented in construction of the property, property characteristics (Age, number of floors, rooms, bathrooms, design, size in M2) and cleanness and safety of neighborhood to be the most important factors effecting the decision of property buyers/tenants with price being the first factor. Other factors that influence the purchase decision which were mentioned by respondents of the survey are closeness of the property to family members and infrastructure of the district. Factors that were considered to be neutral or unimportant for property buyer/tenants were house facilities (Swimming pool, garden, security), closeness of the property to general facilities, mortgage rate and owning a green-sustainable-low energy property.